C H Rautenbach, P S Dreyer en C K Oberholzer: Hulle nalatenskap en die pad vorentoe 1 - Beukes, Johann (Hervormde teologiese studies, 2000)
C H Rautenbach, P S Dreyer and C K Oberholzer: Their legacy and the way ahead. This article explores the legacy of three early philosophers at the University of Pretoria (1939-1987), who contributed substantially to the Nederduitsch Hervormde Kerk's perspectives on the relation between (modern) theology and (modern) philosophy. The authors consider their legacy to be an essentially Kantian stabilisation of the complex and problematic relationship between reason and faith, church and society, and theology and philosophy. The article then proceeds to interpret the changes in these relationships that were brought about by the postmodern discourse.